Investigating Academic Burnout among Final-Year English Education Students: A Case Study Research at IAIN Parepare - Yulie Asni; Nur Ainun Rais; Tri Wulandari (JELITA, 2024)
This study aims to analyze the academic burnout among final-year students of the English education department in the 2023-2024 academic year at IAIN Parepare. Data collection applied survey methods using Maslach Burnout Inventory (MBI) with Likert Scale to 93 final year students who are working on their thesis. Statistical analysis methods used include Kolmogorov-Smirnov for normality testing and Spearman Correlation to measure the relationship between variables. The result shows that the final year students experienced medium level of academic burnout. 57% of them felt emotional exhaustion, 51% realized they were experiencing depersonalization, 52% were exposed to personal achievements. Overall, the data indicates the final year English education students experienced moderate burnout across all dimensions, which significantly impacted their emotional well-being, engagement in academic roles, and personal accomplishment perception. These results suggest that institution should consider implementing more intensive emotional and academic mentoring programs for final year students. This could include counseling, stress management sessions, and psychological support that can help reduce emotional exhaustion and depersonalization. In addition, the supervisors are expected to provide adaptive mentoring, understand individual needs, and help students develop realistic strategies to complete their thesis. These efforts are expected to improve academic well-being, so that students can complete their studies optimally and confidently.